A novel waterborne g‐CPP sizing agent for the interfacial enhancement of SCF/PP composites. Issue 3 (11th January 2022) - Li, Zheng; Wang, Kexin; Liu, Xudong; Hu, Jiaoli; Zhang, Jie; Yang, Guorui; Xie, Ruihang; Zhang, Jialiang; Ao, Yuhui
Abstract: To enhance the interfacial adhesion of short carbon fiber (SCF) reinforced polypropylene (PP) composites, a new modified chlorinated polypropylene resin (g‐CPP) was synthesized and utilized to manufacture the sizing agent for SCF. The findings of thermogravimetric analysis and differential scanning calorimetry showed that g‐CPP had high thermal characteristics, with its glass transition temperature (Tg) raised by 11°C.The g‐CPP sizing agent that has been developed has increased storage stability (particle size was 109.8 nm). The contact angle of SCF was reduced from 81.52° to 60.04° after sizing, and the surface free energy was raised from 29.31 mN/m soared to 47.13 mN/m. The SCF/PP composites with 1 wt% sizing agent demonstrated the best interfacial adhesion, with improvements in flexural and tensile strengths of 54% and 39%, respectively. The interfacial reinforcement mechanism of sizing agent to improve interfacial adhesion was investigated. This work proposes an attractive way for the future preparation of high‐performance SCF/PP composites. Abstract : The chemical structure of chlorinated polypropylene (CPP) is similar to that of PP and its beneficial solubility makes it an easier aqueous sizing agent for PP substrates. However, chlorinated polypropylene also has disadvantages, mainly due to its poor molecular polarity, which results in low solubility in polar solvents. The adhesion of sizing agents prepared from chlorinated polypropylene to carbon fibers is poor. In this study, an attempt was made to adjust the molecular polarity of chlorinated polypropylene by graft modification. A feasible method was designed for the preparation of chlorinated polypropylene/acrylate copolymers in butyl acetate solution. The copolymer (g‐CPP) was then used as the main raw material for the preparation of sizing agent to prepare an aqueous sizing agent to provide well‐compatible interfacial properties.